Systems Transdisciplinary Approach in the General Classification of Scientific Approaches - Mokiy, Vladimir (European Scientific Journal, ESJ, 2019)
The development of systems thinking and systems worldview needs new types of system approaches. New types of systems approaches should find their place in the appropriate classification of scientific approaches. The article attempts to substantiate the natural connection of classical scientific approaches with their system analogues. This relationship is manifested in the General classification of scientific approaches from the mono-disciplinary approach to the systems transdisciplinary approach. The definitions of the approaches in such a classification are distinguished by identification features and functional features. Classification allows you to consciously use these definitions within a single semantic field of scientific knowledge. The streamlining of scientific approaches within the framework of such a classification makes it possible to give a rationale for a wide range of interdisciplinary interactions in modern science.